Konflik Kepentingan antara Manajemen dan Pemilik Perusahaan - Yulekhah Ariyanti; Ratna Kusumawati (AKSES: Jurnal Ekonomi dan Bisnis, 2006)
The article explored the effect of separation between share holder and management  which could make agency problem. The problem was  caused by the agent and the principal as economic agent so they tried holding their interest  and doing moral hazard  for protecting their interest.